Primary study for effects on transdifferentiating rat neonatal cardiomyocytes into pacemarker cells of several Vietnamese plant extracts - Do, Thi Thao; Trieu, Ha Phuong; Nguyen, Thi Nga; Do, Thi Phuong; Nguyen, Thi Cuc; Pham, Thi Hai Yen (Vietnam Journal of Science and Technology, 2020)
Cardiovascular diseases have been accounted for the highest mortality rate worldwide. Sinoatrial node (SAN) dysfunction causes many symptoms from syncope to cardiac arrest, which usually happened in elderly people. Recently, there are many strategies that were developed to support the patient. Electrical pacemaker was known as the standard device that was implanted to induce the electrical pulse, with some limitation of the battery and the lead. Transdifferentiating neonatal cardiomyocytes into pacemaker cells by natural compounds was recognized as a novel design. Following this direction, we studied the neonatal cardiomyocyte transdifferentiating effects of garlic and green teaextracts.Thecardiomyocytes, isolated from neonatal rats, were incubated in 18 hours and exposed with extracts for 24 hours.The garlic and green tea crude extracts or fractions at lower than 100 µg/mL were not toxic for the cells. Among the others, thegarlic ethyl acetate fraction seemed to enhance the beating rate of induced cardiomyocytes at71.33±5.21 beats per minute. This fractionand the ethanol extract from green tea were also able to induce the expression of hyperpolarization-activated cyclic nucleotide-gated channel 4 (HCN4), the important factor for automatic beating of SAN, but insignificantly (P>0.05). In conclusion, neonatal cardiomyocytes were isolated and suitable for use as a model for screening of pacemaker cell transduction effects of potential candidates. From this study, the garlic ethyl acetate fraction presented as the most promising nominee for further neonatal cardiomyocyte transdifferentiating effects.